2010
DOI: 10.1074/jbc.m110.176255
|View full text |Cite
|
Sign up to set email alerts
|

A Post-entry Step in the Mammalian Orthoreovirus Replication Cycle Is a Determinant of Cell Tropism

Abstract: Mammalian reoviruses replicate in a broad range of hosts, cells, and tissues. These viruses display strain-dependent variation in tropism for different types of cells in vivo and ex vivo. Early steps in the reovirus life cycle, attachment, entry, and disassembly, have been identified as pivotal points of virus-cell interaction that determine the fate of infection, either productive or abortive. However, in studies of the differential capacity of reovirus strains type 1 Lang and type 3 Dearing to replicate in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
35
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 57 publications
5
35
0
Order By: Relevance
“…All viruses were generated from plasmids by reverse genetics as described previously (20,38). The recombinant viruses were plaque purified, amplified using L929 cells, purified using CsCl gradients (49), and stored as diluted aliquots at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…All viruses were generated from plasmids by reverse genetics as described previously (20,38). The recombinant viruses were plaque purified, amplified using L929 cells, purified using CsCl gradients (49), and stored as diluted aliquots at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies of T3-infected MDCK cells revealed that inclusions produced by strain T3 display normal morphological and kinetic development despite an apparent functional abnormality leading to arrest of replication (33). To more precisely define viral inclusion composition and ultrastructure in T3-infected MDCK cells, we used both confocal immunofluorescence microscopy and thin-section TEM.…”
Section: Reovirus Replication In Mdck Cellsmentioning
confidence: 99%
“…Strain T1 replicates efficiently, while T3 replicates poorly. Analysis of recombinant reovirus strains derived from reverse genetics revealed that the M1-encoded 2 protein of strain T1 in a T3 genetic background independently promotes reovirus replication in MDCK cells (33). The L1-encoded 3 protein is a modulator of 2 effects on replication efficiency, although 3 does not display an independent association with replication capacity in MDCK cells.…”
mentioning
confidence: 99%
See 2 more Smart Citations